Patient and donor antibody profiles in early COVID-19 convalescent plasma therapy in the COnV-ert trial - Alemany, Andrea; Ouchi, Dan; Pradenas, Edwards; Aguilar, Ruth; Vidal, Marta; Jimenez, Alfons; Millat-Martinez, Pere; Corbacho-Monné, Marc; Suñer, Clara; Bassat, Quique; Baro, Bàrbara; Moncunill, Gemma; et al. (Frontiers in Immunology, 2025)
IntroductionThe negative efficacy results of coronavirus disease 2019 (COVID-19) convalescent plasma (CCP) as early treatment in the COnV-ert trial have been attributed to the use of methylene blue (MB). We characterized immune responses after MB-treated CCP infusion and the impact of MB on antibodies of the infused CCP units.MethodsWe measured antibody isotypes (IgG, IgM, and IgA) and IgG subclasses (IgG1, IgG2, IgG3, and IgG4) against SARS-CoV-2 nucleocapsid and spike (S) antigens, neutralizing antibody titers, and IgG avidity in 128 participants of the COnV-ert trial 7 and 60 days after infusion and in paired CCP units before and after MB treatment.ResultsTreatment with CCP significantly increased the levels of IgG and IgG1 to receptor-binding domain (RBD) and S, IgG3 to S and S2, and IgG avidity in recipients 7 days after infusion, without an increase in IgA, IgM, IgG2, IgG4, or neutralization. At day 7 post-infusion, recipients exhibited lower IgG, all IgG subclasses, and avidity; higher IgA and IgM; and comparable neutralization relative to paired CCP units. MB was associated with a significant decrease in cytophilic subclasses IgG1 and IgG3 to S and S2, and IgA to RBD, S and S2 in CCP units, without a reduction in neutralization titer and with a modest increase in IgG2 to RBD and S.DiscussionOur study shows a modest impact of a single intravenous infusion of MB-treated high-titer CCP on circulating antibody levels compared to those generated by the host by day 7 and an adverse effect of MB on IgG1 and IgG3, which are essential for effector functions.Clinical trial registrationhttps://www.clinicaltrials.gov/, identifier NCT04621123.